Intraperitoneal Microdialysis as a Monitoring Method in the Intensive Care Unit - Konstantinos, Tasiopoulos (Int Surg, 2014)
Studies on surgical patients provide some evidence of prompt detection of enteric ischemia with microdialysis. The purpose of the study was to measure intraperitoneal microdialysis values (glucose, glycerol, pyruvate, and lactate) in patients hospitalized in an intensive care unit (ICU) with an underlying abdominal surgical condition and to correlate these values with patients' outcomes. Twenty-one patients, 10 female, were enrolled in the study. The intraperitoneal metabolite values were measured for 3 consecutive days, starting from the first day of ICU hospitalization. Descriptive and inferential statistics were performed. The t-test, repeated measures analysis, Holm's test, and a logistic regression model were applied. Level of statistical significance was set at P = 0.05. Mean age of participants was 68.10 ± 8.02 years old. Survivors exhibited statistically significantly higher glucose values on day 3 (6.61 ± 2.01 against 3.67 ± 1.62; P = 0.002). Mean lactate/ pyruvate (L/P) values were above 20 (35.35 ± 27.11). All non-survivors had a mean three day L/P values greater than 25.94. Low L/P values were related to increased survival possibilities. High microdialysis glucose concentration, high L/P ratio and low glucose concentration were the major findings during the first three ICU hospitalization days in non-survivors. Intraperitoneal microdialysis may serve as a useful tool in understanding enteric ischemia pathophysiology.